Development of an eco-protocol for seaweed chlorophylls extraction and possible applications in dye sensitized solar cells. (24th June 2016) - Armeli Minicante, S; Ambrosi, E; Back, M; Barichello, J; Cattaruzza, E; Gonella, F; Scantamburlo, E; Trave, E
Abstract: Seaweeds are a reserve of natural dyes (chlorophylls a, b and c ), characterized by low cost and easy supply, without potential environmental load in terms of land subtraction, and also complying with the requirements of an efficient waste management policy. In particular, the brown seaweed Undaria pinnatifida is a species largely present in the Venice Lagoon area, and for it a removal strategy is actually mandatory. In this paper, we set-up an eco-protocol for the best extraction and preparation procedures of the pigment, with the aim of finding an easy and affordable method for chlorophyll c extraction, exploring at the same time the possibility of using these algae within local sustainable management integrated strategies, among which the possible use of chlorophylls as a dye source in dye sensitized solar cells (DSSCs) is investigated. Experimental results suggest that the developed protocols are useful to optimize the chlorophyll c extraction, as shown by optical absorption spectroscopy measurements. The DSSCs built with the chlorophyll extracted by the proposed eco-protocol exhibit solar energy conversion efficiencies are similar to those obtained following extraction protocols with larger environmental impacts.